The secret ingredient - Schaefer, Laura (Simon & Schuster Books for Young Readers, 2011)
While working at her grandmother's Madison, Wisconsin, teashop, fourteen-year-old Annie hears of a scone cook-off, for which the prize is an all-expense paid trip to London for tea, and enlists Genna and Zoe to help her win. Includes proverbs, quotations, and brief stories about tea, as well as recipes.